Expression of CA2 and CA9 carbonic anhydrases in ulcerative colitis and ulcerative colitis‐associated colorectal cancer. Issue 8 (14th May 2020) - Nakada, Norihiro; Mikami, Tetuo; Horie, Kayo; Nagashio, Ryo; Sakurai, Yasutaka; Sanoyama, Itaru; Yoshida, Tsutomu; Sada, Miwa; Kobayashi, Kiyonori; Sato, Yuichi; Okayasu, Isao; Murakumo, Yoshiki
Abstract : Ulcerative colitis (UC) is characterized by chronic inflammation in the colonic mucosa and submucosa with repeating relapse and remission, but the pathogenesis is unknown. Patients with long‐standing UC are at high risk of neoplasm development. The aim of the present study was to identify molecules whose expression is associated with UC and UC‐associated colorectal cancer (UCCA). Biopsy specimens from UC and normal colonic mucosae were analyzed using a proteomics approach, in which carbonic anhydrase 2 (CA2) was identified as a molecule downregulated in UC mucosae. Immunohistochemically, CA2 expression was detected in normal and diverticulitis mucosal epithelia, and its expression decreased as UC activity increased. CA2 expression was almost undetectable in UCCA. We also analyzed the expression of another carbonic anhydrase, CA9, and its upstream molecule, hypoxia‐inducible factor‐1α (HIF‐1α), both of which are induced under hypoxic conditions. It was revealed that CA9 expression was relatively low in normal, diverticulitis and UC mucosae, and was upregulated in UCCA. HIF‐1α expression was consistently low in all tissue types examined. In conclusion, these results suggest that CA2 and CA9 may be possible indicators of UC activity and UCCA development, respectively.